A causal model of the impact of the "fuzzy front end" on the success of new product development - Cornelius Herstatt; Birgit Verworn (Hamburg University of Technology (TUHH), Institute for Technology and Innovation Management (TIM), 2000)
In a study of New Product Development (NPD) projects, the fuzzy front end of innovation is explored. The New Product Development process is a multistage process. Therefore, the study examines two sorts of impact that the fuzzy front end has on the success of New Product Development: a direct impact and an indirect impact by influencing the next stage of the NPD process, i.e. project execution. Furthermore, the degree of newness of the NPD projects in accordance with the contingency theory, is considered. We develop and test a causal model of relationships among key variables related to the fuzzy front end, project execution, and success. The causal model is tested with AMOS using information from 144 completed projects from German measurement and control technique firms. For the most part, the responses from these firms support the hypothesized relationships. The frequently claimed importance of the fuzzy front end is confirmed. The results offer strong support for the importance of the early involvement of all functions in an NPD effort to enhance communication and ultimately project success. This can be advanced by a draft initial planning prior to development. Furthermore, the responses highlight the importance of reducing market and particularly technical uncertainty during the fuzzy front end, both of which have a negative influence on communication and increase deviations during project execution. The technical uncertainty that remains at the start of the project has a direct, negative influence on project efficiency and overall it has the most far reaching implications for the success of the project. With regard to contingency theory, the results indicate that effort spent on the reduction of uncertainty for improving project execution and project success may be influenced by the degree of newness. The degree of newness is found to influence the reduction of technical uncertainty, deviations from specifications, and efficiency. Overall, the results of this study support previous research regarding the strong influence that front end activities have on NPD success. The model presented here provides several insights that can help managers to improve their NPD success and inspire researchers to carry out further studies regarding the fuzzy front end.
urn:nbn:de:gbv:830-opus-1410
Keywords: 650; New Product Development; fuzzy front end